Rancangan Aplikasi Customer Service Pada PT. Lancar Makmur Bersama - -, Suryasari; Callista, Astrid; Sari, Juwita Sari (Major of Information Systems Faculty of Computer Science Sriwijaya University, 2012)
This research is based on the need of an organized customer service system for PT. Lancar Makmur Bersama. PT. Lancar Makmur Bersama is a company that engaged in sales engineering tools. This company has many customers, therefore the customer service would be necessary to regulate and maintain good relationships with customers.The main problem faced by this company is often complaint from customers is not responded properly and information about the complaint is not documented. In addition, the activity of selling goods to customers are also not recorded properly. This research produced a system design using prototyping methods, and UML (Unified Modeling Language). The designed system could organized and documenting every complaints, feedbacks, and questions from customers, so that if there is problem that can be followed immediately.Key Word : Customer Service Application